Synthesis of silver nanoparticles (AgNPs) using Ficus retusa leaf extract for potential application as antibacterial and dye decolourising agents. Issue 11 (2nd November 2017) - Singhal, Anjum; Singhal, Nikita; Bhattacharya, Amrik; Gupta, Anshu
ABSTRACT: Synthesis of AgNPs was attempted using aqueous Ficus retusa leaf extract (FRLE). The effects of silver nitrate concentrations, FRLE volume, initial pH and temperature on synthesis were also studied. TEM revealed the size of AgNPs in range of 5–35 nm and crystal structure was confirmed by XRD. FTIR showed the capping of AgNPs by biomolecules of FRLE. Zeta potential of −39.1 indicates good stability of AgNPs. The AgNPs were evaluated for their antibacterial and high catalytic activity in enhancing decolourisation of eriochrome black T dye in presence of sodium borohydride (from 19.74 to 86.05%) and light source (from 41.96 to 80.11%).